Risk Assessment of the Impact of Oil Spill on the Heavy Metal Content of Santa Barbara River in Bayelsa State, Nigeria - Iyama, William Azuka; Egbunefu, Chukwudi Omeni; Nakara, Timothy; Emejuru, Stella; Nwagbara, Victor Uzoma (Universitas Negeri Semarang, 2023)
This study was aimed at assessing both the effect (risk) and impact of a recent oil spill on heavy metal concentration in the Santa Babara River in Bayelsa State, Nigeria. Samples were collected and preserved based on standard methods. The heavy metals of interest were Mercury (Hg), Arsenic (As), Cadmium (Cd), Chromium (Cr) and Copper (Cu) due to their levels of toxicities and presence in water bodies while the five study stations were Worokuma (W), Uwanga (W), Tuweni (T), Shellikiri (S), Inarakiri (I) and Esenfakiri (E). The solar thermos elemental flame atomic absorption spectrometer (AAS), model SE-71096 made in Germany with detection limit of 0.001 mg·kg−1 was used for the heavy metal analysis. The trend of heavy metal abundance was found in this order Cr>Cu>Cd>Pb>Hg=As. All the detectable metals had risk index of greater than 5 but the highest was found in the order, Cd> Pb > Cu > Cr (149, 35, 26 and 12 respectively) which meant extremely high level of pollution. This also indicated the probability of non-carcinogenic effects occurring and increases as HI increases signifying carcinogenic risk via direct ingestion of water. Graphs were used to show trends in both mean heavy metal concentrations and risk assessment indices. Chromium and Pb had moderate contaminations for CF and CDI values, hence regular monitoring of the Santa Barbara River is of essence as most of the inhabitants take this as the only source of potable water as their wells have very high iron content.